CBAM! - Assessing potential costs of the EU carbon border adjustment mechanism for emerging economies - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
With the EU adopting more ambitious emission reduction targets this year, the European Commission in July published a proposal on measures for adjusting EU climate policy. Measures include a carbon border adjustment mechanism (CBAM) that imposes a price on emissions embodied in products imported to the EU. In this policy note, we review the main lines of the CBAM proposal and discuss its potential economic effects on China, India, Russia, Turkey and Ukraine – the EU's largest import sources for products subject to CBAM. We calculate illustrative estimates for the potential cost effectsof several specifications of the CBAM for these countries and compare them against earlier estimates. We also discuss the potential aggregate economic effects of the CBAM for these economies based on earlier literature. Despite considerable variation across countries and sectors, our analysis suggests that the aggregate economic effects of the CBAM would be limited for most exporting countries.
urn:nbn:fi:bof-202110252070
Keywords: 330; carbon border adjustment mechanism; climate policy; international trade; emerging economies